Relationship between Maternal Vitamin D Level and Small for Gestational Age Infant in West Java, Indonesia - Setyorini Irianti; Raden Tina Dewi Judistiani; Sylvia Rachmayati; Jusuf Sulaeman Effendi; Budi Setiabudiawan (Faculty of Medicine, Universitas Padjadjaran, 2020)
Small for gestational age (SGA) infants is one of the unfavorable outcomes of pregnancy that needs to be prevented. There are not many studies available on the association of maternal vitamin D levels during pregnancy and SGA infants. This study aimed to discover the association between maternal vitamin D level and SGA infants in West Java. A cohort study was performed from February 2018 to January 2019 by recruiting 304 pregnant women in Bandung, Cimahi, Waled, and Sukabumi, West Java Province, Indonesia. Of that number, 203 women were followed until the delivery date. Data were collected from the results of serial ultrasonography examinations and maternal vitamin D level measurements. Bivariate analysis and logistic regression were then performed to determine the relationship between variables. This study showed that 30 of 203 (14.78%) infants were born as SGA infants. The mothers of these SGA infants had a lower maternal vitamin D level at the beginning of the second trimester and smaller anthropometric measurements at the beginning of the third trimester. However, no significant difference was found between normal infants and SGA infants when the overall values for all trimesters were compared. It can be inferred that the maternal vitamin D level has a negative relationship with SGA infants in West Java, Indonesia. Further studies are required to prove the relationship between maternal vitamin Dl level and SGA infants.Hubungan Kadar Vitamin D Ibu dan Bayi Kecil Masa Kehamilan di Jawa BaratBayi kecil masa kehamilan (KMK) adalah luaran kehamilan yang perlu dicegah. Informasi tentang hubungan kadar vitamin D ibu dengan kejadian bayi KMK di Indonesia masih terbatas. Kadar vitamin D dan karakteristik ibu diduga berpengaruh dalam kejadian bayi KMK. Tujuan penelitian ini adalah mengetahui hubungan kadar vitamin D ibu dengan kejadian KMK pada bayi. Studi kohort dilakukan dari Februari 2018 hingga Januari 2019 dengan merekrut 304 ibu hamil di Bandung, Cimahi, Waled, dan Sukabumi, Provinsi Jawa Barat, Indonesia. Dari jumlah 203 orang diantaranya berhasil diikuti sejak trimester satu hingga persalinan dan terpilih menjadi subjek penelitian kasus kontrol. Pemeriksaan ultrasonografi, kadar vitamin D dan hemoglobin ibu dilakukan serial tiap trimester. Dilakukan analisis bivariat dan regresi logistik untuk menentukan hubungan antar variabel yang diteliti. Dari penelitian ini didapatkan sebanyak 30 dari 203 (14,78%) persalinan dengan luaran bayi KMK. Bayi KMK cenderung mempunyai riwayat kadar vitamin D yang lebih rendah pada awal trimester kedua dan hasil antropometri yang lebih rendah pada awal trimester tiga, namun secara statistik tidak berbeda signifikan. Simpulan penelitian ini bahwa kadar vitamin D ibu hamil memiliki korelasi negatif dengan bayi KMK. Penelitian lebih lanjut diperlukan untuk membuktikan hubungan antara kadar vitamin D ibu dan bayi KMK.